A genetic algorithm to solve the thermal unit commitment problem. (29th October 2014) - Labbi, Yacine; Benattous, Djilani
In this paper, a genetic algorithm (GA) is proposed to solve the thermal unit commitment (UC) problem. The objective of UC is to determine the optimal generation of the committed units to meet the load demand and spinning reserve at each time interval, such that the overall cost of generation is minimised, while satisfying different operational constraints. The results obtained show that, with the application of the proposed method (GA) to the unit commitment problem, better convergences and solutions are obtained than with other metaheuristic algorithms.